Evaluation of yield And morphology traits in 72 genotypes Of sainfoin (Onobrychis Viciifolia Scop) through factor analysis - Mohajer, S.; Jafari, A.A.; Taha, R.M.; Ahmed, A.B.A. (2012)
Seventy two genotypes of sainfoin (Onobrychis viciifolia Scop) were sown using lattice design under irrigation condition in Alborz, station Karaj, Iran during 2009-10. Forage dry mater (DM) yield, leaf to stem ratio, growth condition, stem density, plant height, flowering time and resistance to sainfoin powder mildew were studied over 2 years. The analysis of variance showed significant differences for all traits (P<0.01). The correlation coefficient between DM yield and growth condition, plant height and stem density was positive and significant. Resistance to disease had negative significant relationship with late-growing, plant height, stem density and forage yield. In addition, Ward cluster analysis was done and divided into 4 genotype groups. In coordinate axis, 1st and 2nd factors demonstrated a good agreement between cluster and factor analysis.